2018
DOI: 10.3960/jslrt.18011
|View full text |Cite
|
Sign up to set email alerts
|

The clinical impact of human T-lymphotrophic virus type 1 (HTLV-1) infection on the development of adult T-cell leukemia-lymphoma (ATL) or HTLV-1–associated myelopathy (HAM) / atypical HAM after allogeneic hematopoietic stem cell transplantation (allo-HSCT) and renal transplantation

Abstract: Because there are limited clinical reports on the impact of human T-lymphotropic virus type 1 (HTLV-1) on organ transplantation, its effects on the development of adult T-cell leukemia-lymphoma (ATL), post-transplantation lymphoproliferative disorder (PTLD) and HTLV-1-associated myelopathy (HAM) or atypical HAM after organ transplantation remain unclear.We retrospectively analyzed the impact of HTLV-1 in 54 allogeneic hematopoietic stem cell transplantation (allo-HSCT) cases and 31 renal transplantation cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
0
6
0
1
Order By: Relevance
“…Furthermore, recently, a small but not negligible number of cases of the development of ATL from HTLV-1-positive recipients undergoing strong immunosuppressive treatment after living-donor renal and liver transplantation have been reported from not only Japan but also other countries (Kawano et al, 2006(Kawano et al, , 2018Yoshizumi et al, 2012Yoshizumi et al, , 2016Martin et al, 2014;Cook et al, 2016;Motomura et al, 2019;Yamauchi et al, 2019). One of these, Yoshizumi et al (2012) reported five patients with transplantation-related ATL after intervals of 181-1,315 days among 82 living donor liver-transplant recipients who were asymptomatic HTLV-1 carriers prior to transplantation.…”
Section: Immunosuppressive Status Including Organ Transplantationmentioning
confidence: 99%
“…Furthermore, recently, a small but not negligible number of cases of the development of ATL from HTLV-1-positive recipients undergoing strong immunosuppressive treatment after living-donor renal and liver transplantation have been reported from not only Japan but also other countries (Kawano et al, 2006(Kawano et al, , 2018Yoshizumi et al, 2012Yoshizumi et al, , 2016Martin et al, 2014;Cook et al, 2016;Motomura et al, 2019;Yamauchi et al, 2019). One of these, Yoshizumi et al (2012) reported five patients with transplantation-related ATL after intervals of 181-1,315 days among 82 living donor liver-transplant recipients who were asymptomatic HTLV-1 carriers prior to transplantation.…”
Section: Immunosuppressive Status Including Organ Transplantationmentioning
confidence: 99%
“… 18 ATL recurs owing to the growth of recipient-derived ATL cells after allo-HSCT. 19 Thus, these results suggest that donor-derived HTLV-1-infected CD8 + T lymphocytes were not cancerous in this case because of the short period of transformation to ATL cells, although HTLV-1 transmission can occur from recipient cells to donor cells. 20 …”
Section: Discussionmentioning
confidence: 56%
“…La normatividad colombiana establece claramente la obligatoriedad de la tamización para HTLV-1 y 2 en donantes de órganos, sin embargo, este estudio mostró que no se cumple en su totalidad la norma y por lo tanto, queda parte de la población que recibe órganos con fines de trasplante, expuesta a un riesgo de infección (14). La infección por estos virus en los receptores de órganos se ha relacionado con la aparición de mielopatía (TSP), desorden proliferativo posterior a trasplante (una forma de linfoma en pacientes trasplantados), o ATLL, tanto en pacientes con trasplantes de médula ósea como en trasplantes de órganos sólidos (20,21). Incluso se ha documentado la ocurrencia de casos en España a partir de donantes colombianos como lo describe Mendoza y cols (21).…”
Section: Discussionunclassified